2016
DOI: 10.1007/s10528-016-9733-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase VI Gene Polymorphism rs2274327 Relationship Between Salivary Parameters and Dental-Oral Health Status in Children

Abstract: The aim of this study was to research carbonic anhydrase (CA) VI one single-nucleotide polymorphism (SNP) and its potential association with dental-oral health status (dental caries, Plaque Index (PI) and Gingival Index (GI)) and salivary parameters (salivary buffering capacity, salivary flow rate (SFR)) in children. A total of 178 children were divided into two groups: non-carious (n = 70, 34 boys and 36 girls) and carious (n = 108, 47 boys and 61 girls). The clinical evaluations were performed according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Although the physiological role of CA VI has not been established, it may be required for oral homeostasis to regulate against acidic environments [ 170 ]. Maintenance of proper pH levels in the saliva protects against enamel erosion and acid neutralization in biofilms and prevents dental caries [ 171 , 178 , 179 , 180 ]. Inhibition of CA VI was shown to cause taste perversion and sometimes complete loss of taste [ 173 , 181 ].…”
Section: Secreted Ca Isoforms: Expression Distribution and Functmentioning
confidence: 99%
“…Although the physiological role of CA VI has not been established, it may be required for oral homeostasis to regulate against acidic environments [ 170 ]. Maintenance of proper pH levels in the saliva protects against enamel erosion and acid neutralization in biofilms and prevents dental caries [ 171 , 178 , 179 , 180 ]. Inhibition of CA VI was shown to cause taste perversion and sometimes complete loss of taste [ 173 , 181 ].…”
Section: Secreted Ca Isoforms: Expression Distribution and Functmentioning
confidence: 99%
“…Individuals with a variant G allele showed differential fungiform papillae density and morphology, and the variant G allele modified the intensity of bitterness both on its own and in concert with the TAS2R38 haplotype [16]. The variant CAVI protein also showed an association with the risk of caries and other oral health parameters [21, 22]. Moreover, some CA isozymes are thought to be associated with unregulated cell proliferation and malignancy invasion [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, several studies in humans have indicated that polymorphisms in genes involved in enamel formation [Patir et al, 2008;Kang et al, 2011;Shimizu et al, 2012;Tannure et al, 2012;Saha et al, 2015], saliva composition [Anjomshoaa et al, 2015;Sengul et al, 2016], and immune response [Bagherian et al, 2008;Azevedo et al, 2010;Valarini et al, 2012;Fine et al, 2013], including DEFB1 [Ozturk et al, 2010;Krasone et al, 2014;Yildiz et al, 2016], play a role in caries susceptibility.…”
mentioning
confidence: 99%